Aircraft design : a systems engineering approach - Sadraey, Mohammad H. (Hoboken, New Jersey : Wiley, 2012)
"Presenting in one volume the methodologies behind aircraft design, this book uses a systems engineering approach to cover the components and the issues affected by design procedures. The basic topics that are essential to the process, such as aerodynamics and controls, are covered first of all. The author then explains the design process in a holistic manner to emphasize the integration of individual components into the overall design. Throughout the book, the various design options are considered and weighed against each other, to give readers a practical understanding of the process overall"--
"Presenting in one volume the methodologies behind aircraft design, this book uses a systems engineering approach to cover the components and the issues affected by design procedures"--
1. Aircraft design fundamentals -- 2. Systems engineering approach -- 3. Aircraft conceptual design -- 4. Preliminary design -- 5. Wing design -- 6. Tail design -- 7. Fuselage design -- 8. Propulsion system design -- 9. Landing gear design -- 10. Weight of components -- 11. Aircraft weight distribution -- 12. Design of control surfaces -- Appendices.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Airplanes -- Design and construction; Airplanes -- Design and construction; TECHNOLOGY & ENGINEERING -- Aeronautics & Astronautics; Airplanes -- Design and construction; Airplanes / Design and construction; Electronic books; Electronic books